ATRX in Diffuse Gliomas With its Mosaic/Heterogeneous Expression in a Subset. (13th June 2016) - Purkait, Suvendu; Miller, Christopher A.; Kumar, Anupam; Sharma, Vikas; Pathak, Pankaj; Jha, Prerana; Sharma, Mehar Chand; Suri, Vaishali; Suri, Ashish; Sharma, B.S.; Fulton, Robert S.; Kale, Shashank Sharad; et al.
Abstract: This study aims (1) to evaluate ATRX expression in different grades and subtypes of gliomas and correlate with other hallmark genetic alterations, (2) to identify and characterize mosaic/heterogeneous staining in gliomas in terms of mutation status. One hundred seventy six cases of glioma were assessed for ATRX immunohistochemistry and subdivided into positive, negative and mosaic/heterogeneous staining patterns. Five cases with heterogeneous staining were further subjected to next generation sequencing. Higher frequency of ATRX immune‐negativity was detected in grade II/III astrocytic, oligoastrocytic tumors and secondary glioblastomas (GBMs), while infrequent in primary GBMs and rare in oligodendrogliomas. Loss of expression was significantly associated with IDH1 and/or TP53 mutation, while mutually exclusive with 1p/19q codeletion. Mosaic/heterogeneous staining was detected exclusively in GBMs (21.2%). Two different types of mosaic staining were identified (1) Admixture of positive and negative nuclei or intermixed mosaic and (2) Separate fragments with positive and negative/intermixed mosaic staining. ATRX mutation was identified in 2/5 (40%) cases with mosaic staining while one case showed DAXX mutation. All these cases were characterized by distinctly separate immune‐negative and positive/intermixed foci. Hence, it is suggested that cases with heterogeneous staining (especially those with distinctly negative fragments) should be subjected to mutation analysis.